Service Brand Equity: Cross-Sectional Analysis of Four Service Schemes in Malaysia - Sharizal, Hashim; Ernest, Cyril deRun (2013)
It has been noted in the literature, service brand is considered to be one of the most discussed in the service industry. Because service is dominated by experience and credence attributes; therefore an extrinsic cue like brand may help to reduce customers’ purchase risk and optimize their cognitive processing abilities towards the service. One of the emerging service brand concepts that used extensively by marketing reseachers is service brand equity. However, there is limited interest looking at the broader application of service brand equity concept across different service categories. This is important to provide service marketers with useful and broader managerial insights in order to establish greater brand managerial sophistication in marketing the services. Hence, the aim of this research is to determine the dimensions of a successful branding strategy of services, to note each specific service sectors requirement, and its differences. The survey method is used in this study. The findings showed that different service category such as health service, retail, hotel and banking in Malaysia posited different dimension of service brand equity. This tends to suggest that, although service brand equity concept provides a significant description of how to brand a service; different services require different approach of branding process. Thus, this may help brand managers to prioritize and allocate which brand equity dimensions is suitable for their service. The principal contribution of the study is that it provides evidence for the validity of service brand equity used in various service contexts.